(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Education leads toenlightenment and learning leads to modification of behavior. The process ofteaching- learning must be joyful and interesting. Learning, when it is coupledwith the students’ motivation, readiness, exercise and effect. i.e theprinciples of learning , may result into a sound learning. The researcher here,in the present research topic ‘Learn While Play’, tries to explore thecomparative effectiveness of teaching through childhood games and teachingthrough traditional approaches. The experiment has been conducted on two equalsections, equal mean scores on achievement level of classes First to Third inall subjects - English, Hindi, Maths and EVS. One section is taught throughtraditional approaches and the second one by engaging students in childhood gameswhich the students have been playing before their schooling starts or in theearly years of their schooling. In the present study such 53 games have beenidentified, according to the nature of the learning units. At the end of theteaching-learning process ‘multiple choice achievement tests’ have beenadministered in all the subjects and to all the classes. It is concluded thatthe students, taught through childhood games learnt better in all subjects.Secondly, they are happy, taking interest in their studies, involve themselvesin the teaching- learning process more voluntarily and willingly, and theteaching-learning atmosphere is lively in comparison to the classroomatmosphere of teaching through traditional approaches. The concepts of timetable, classroom and teacher are to be modified according to the nature ofteaching –learning units.